2021
DOI: 10.1167/tvst.10.9.2
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for Converting Perimetric Sensitivity From Full Threshold and SITA Fast to SITA Standard in Patients With Glaucoma and Healthy Subjects

Abstract: The purpose of this study was to develop nomograms for converting Full Threshold (FT) and Swedish Interactive Threshold Algorithm (SITA) Fast (SF) tests to SITA Standard (SS) tests with the Humphrey Field Analyzer in patients with glaucoma and healthy subjects.Methods: One eye each of 49 patients with glaucoma and 50 healthy subjects was tested in 4 and 2 sessions (each containing the 3 strategies), respectively, over 4 weeks. The difference between pointwise Best Available Estimate (BAE; mean of all FT tests)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Sensitivity values from the full-threshold and SITA strategies are not interchangeable (the full-threshold strategy yields lower sensitivity values compared with the SITA standard strategy) . Therefore, we converted values obtained using the full-threshold strategy to SITA standard equivalents using recently described nomograms . In brief, for each visual field test, we converted the pointwise sensitivity values using the appropriate nomogram for either patients with glaucoma or healthy participants.…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity values from the full-threshold and SITA strategies are not interchangeable (the full-threshold strategy yields lower sensitivity values compared with the SITA standard strategy) . Therefore, we converted values obtained using the full-threshold strategy to SITA standard equivalents using recently described nomograms . In brief, for each visual field test, we converted the pointwise sensitivity values using the appropriate nomogram for either patients with glaucoma or healthy participants.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, both statistically significant variables and clinically significant variables were included in the multivariate logistic regression analysis, and the nomogram model was constructed using the statistically significant variables selected at last (P < 0.05). 15 , 24 , 25…”
Section: Methodsmentioning
confidence: 99%
“…At present, more and more researchers have made a lot of efforts to build prediction models or improve existing prediction models. 15–17 among which building nomogram is one of the hottest research directions. In the latest research, 15 , 18 , 19 the use of nomogram prediction has shown good performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation